2020
DOI: 10.1093/ecco-jcc/jjaa140
|View full text |Cite
|
Sign up to set email alerts
|

International Organization for the Study of Inflammatory Bowel Disease: Global Strategies for Telemedicine and Inflammatory Bowel Diseases

Abstract: Before the onset of the COVID-19 pandemic, the majority of care for inflammatory bowel disease patients was provided in-person. The practice of gastroenterology care has since rapidly transformed, with telemedicine emerging as an essential tool to provide medical care to patients while maintaining social distancing and conserving personal protective equipment. This article provides insight into past and current practices among inflammatory bowel disease specialists and shares regulatory, financial and practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
(5 reference statements)
0
28
0
Order By: Relevance
“…Today it is COVID-19, but in the future, it could be some other virus, especially as we are now more than ever aware of our susceptibility to a viral pandemic. IOIBD/ECCO issued a summary of the best strategies for IBD management via telemedicine, carefully covering every aspect of the patient-physician relationship[ 101 ]. Another very important aspect of telemedicine is its inexpensiveness.…”
Section: The Impact Of the Covid-19 Pandemic On Ibd Management: Present And Future Perspectivesmentioning
confidence: 99%
“…Today it is COVID-19, but in the future, it could be some other virus, especially as we are now more than ever aware of our susceptibility to a viral pandemic. IOIBD/ECCO issued a summary of the best strategies for IBD management via telemedicine, carefully covering every aspect of the patient-physician relationship[ 101 ]. Another very important aspect of telemedicine is its inexpensiveness.…”
Section: The Impact Of the Covid-19 Pandemic On Ibd Management: Present And Future Perspectivesmentioning
confidence: 99%
“…The rapid and widespread innovation of health care delivery from the pre-pandemic era was not without precedent; ( 33 ) Crohn’s and Colitis Canada had already developed the Promoting Access and Care through Centers of Excellence (PACE) Telemedicine Program in Ontario ( 34 ). Moreover, during the pandemic, studies of people with IBD and health care providers identified increased satisfaction, improved outcomes, and greater efficiency with the health care innovations (e.g., Telemedicine) such that the future of IBD care will most likely comprise hybrid models of in-person and virtual health care delivery ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…They question our "pre-pandemic" paradigms around aspects of health care delivery. 8,9 The near universal adoption of telemedicine and components needed for its delivery have been available even in the pre-pandemic era severe COVID-19 outcomes. 10,11 Also, that clinically active IBD at the onset of viral infection is a strong independent risk factor for | 265 INVITED EDITORIAL serious infection, making it imperative for clinicians to factor IBD severity and activity into individual treatment choices in the light of evolving knowledge.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…Even as a growing body of literature supports these initiatives, 3,4,6,7 their findings early in the pandemic need to be taken in context. They question our “pre‐pandemic” paradigms around aspects of health care delivery 8,9 . The near universal adoption of telemedicine and components needed for its delivery have been available even in the pre‐pandemic era but have been underutilised by healthcare professionals, particularly by doctors for out‐patient services and communication between professionals.…”
mentioning
confidence: 99%